Development of Goat - Palm Oil Integrated Production System : An Assessment Based on Feed Availability and Nutrient Requirements - Ginting, Simon P (Indonesian Animal Sciences Society, 2006)
The integration of goats and palm oil plantation is prospective agricultural production systems that exploit the complement relationship among various components in the system . The main components are the oil palm trees, vegetation underneath the trees, processing plant of palm oil bunch, and the goat . The estimation of carrying capacity of the plantation system is based on the quantitative analysis on nutrient supply from various feed resources in the plantation system and nutrient requirements for goat production . The goat demographic parameters, such as, prolificacy, fertility and fecundity are used to estimate the goat population size, dynamics and structures . The development of production model could be based on a certain production target, such as the number of animals sold or the amount of income (demand driven approach), or based on the availability of certain resources such as feed supply (supply driven approach) . Using the demand driven approach, and considering 6000 heads of oneyear old goats to fill the Malaysian market as the production target, it is calculated that a population size of 3,636 does and 810 ha of palm oil plantation are required to meet this production target . In a typically medium-size oil palm plantation system (500 ha of oil palm plantation) with one unit of small-scale palm oil bunch processing plant ( l ton/hour), the potency to supply metabolisable energy from various feed resources in the system is 2,778,800 Mcal/year, equivalent to a carrying capacity of 5,155 Goat Units/year . This system could carry 2,951 does and 295 bucks to produce 1,116 heads of one-year old goats annually . A medium-size oil palm plantation without processing plant unit, is potential in supplying metabolisable energy of 1,983,300 Mcal/year, equivalent to a carrying capacity of 3,680 Goat Units/year . In order to fill the export market to Malaysia, a number of 10 units of medium sized plantation with small scale plant processing or a number of 17 units medium scale plantation without processing unit are required . Using similar approach, the potential of either large-scale or small-scale plantation system to produce goat in an integrated-production system could be estimated . Key words : Integration, palm oil plantation, carrying capacity, goat